STUDI KEPUSTAKAAN: PERAN KOMIK DALAM MEMBANGUN PENGETAHUAN BENCANA DAN SIKAP PEDULI LINGKUNGAN SISWA SEKOLAH DASAR - Syaflita, Dina; Siregar, Hesty Mawarni; Arif, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
Reading materials for elementary school students need to be adapted to the level of cognitive development at the concrete operational level. One source of reading that is suitable and liked by students is comics. The purpose of this study is to theoretically examine the role of comics in learning in order to increase knowledge and attitudes towards environmental care. This type of research is library research. Literature research has a data collection method by taking data from various references, reading, taking notes, and processing research materials. The data collection technique in this study was to find data from various references related to research problems. The instrument used is a checklist for the classification of research materials. The results showed that educational comics could increase students' knowledge of disaster mitigation. This is because the non-fiction elements in the mitigation concept that are packaged in visuals and fictional storylines can make students enjoy reading. The concept of disaster mitigation in comics can also foster an environment care attitude.